Unlocking Organic Agroindustry Employee Eco-Innovation: Role of Green Product Knowledge and Green Transformational Leadership - Irawan, Norbertus Citra; Esthi, Raniasari Bimanti; Wijayanti, Irene Kartika Eka; Widodo, Zandra Dwanita; Darmaningrum, Kurniawati (Indonesian Journal of Economics, Social, and Humanities, 2023)
The problem to be answered in this study is whether green product knowledge (GPK) affects eco-innovation through the mediation of green transformational leadership (GTL) in the processed organic food agroindustry. This research is important because processed organic food is one of the solutions to provide healthy food products for the community and has a broad impact on environmental sustainability through environmentally friendly production practices. The basic research method is an explanatory case study; the data collection technique uses the interview method by distributing 175 questionnaires to 35 agroindustry MSMEs of processed organic food products. Only 150 questionnaires are filled in to be analyzed further, and data analysis uses partial least square. Based on the research results, the first finding is that GPK positively and significantly affects GTL. The second finding is that GPK positively and significantly affects eco-innovation in the processed organic food agroindustry (EI). The third finding is that GTL positively and significantly affects EI. The fourth finding is that GPK positively and significantly affects EI mediated by GTL.